Preparation of polymeric-ceramic composite membranes for use in the methanol synthesis reaction - Elvira, I.; Lasobras, J.; Soler, J.; Herguido, J.; Menéndez, M. (Frontiers in Membrane Science and Technology, 2023)
A new kind of ceramic-polymeric membranes has been prepared and characterized towards its use in membrane reactors for synthesis of methanol from CO2 and hydrogen. In this way, PBI membranes were prepared on a ceramic support by varying parameters of the preparation process. The effect of those parameters on the separation of the compounds involved in the reaction was measured under conditions (temperature, pressure and gas composition) simulating those of the reaction. The prepared membranes were able to selectively remove water from a mixture containing hydrogen and CO2. H2O/CO2 and H2O/H2 separation factors over 18 and 12, respectively, were achieved at 160ºC. The separation factors decreased by increasing the temperature with a 3-layer membrane but were quite stable with a 4-layer membrane.